197 AGING-RELATED ACCUMULATION OF O-GLCNACYLATED PROTEINS IN THE CARDIOVASCULAR SYSTEM. Issue 1 (1st January 2007) - Miller, A. P.; Robertson, C.; Xing, D.; Li, P.; Chen, Y. F.; Chatham, J. C.; Oparil, S.
Abstract : Background: Excessive post-translational modification of nucleocytoplasmic proteins by the addition of O-linked β- N -acetylglucosamine (O-GlcNAc) to Ser and Thr residues by the enzyme O-GlcNAc transferase (OGT) is a proposed mechanism for diabetogenic injury to the cardiovascular system. The current study tested the hypothesis that O-GlcNAcylation exhibits aging-related alterations in the cardiovascular system in normal aging rats. Methods: Young (10 weeks old) and aged (22 months old) female Sprague-Dawley rats were sacrificed, serum was collected, and tissues (carotid artery, heart, liver, and brain) were harvested for assessment of serum glucose, insulin, estradiol, and lipid profiles and for quantification of tissue OGT and O-GlcNAc levels by Western blot analysis. Results: Serum glucose and tissue OGT expression were not significantly different in young and aged animals. Aged animals demonstrated significantly greater O-GlcNAcylated protein expression compared with young rats in carotid arteries and heart but not in liver and brain. Conclusions: There are tissue-specific, aging-related accumulations of O-GlcNAcylated proteins in cardiovascular tissues that are not accounted for by changes in glucose or OGT expression. The chronic accumulation of O-GlcNAcylated intracellular proteins may contribute to the adverse effects of age in the cardiovascular system.